Primary Cutaneous B-Cell Lymphoma: An Update on Pathologic and Molecular Features - Marco Lucioni; Sara Fraticelli; Giuseppe Neri; Monica Feltri; Giuseppina Ferrario; Roberta Riboni; Marco Paulli (Hemato, 2022)
Primary cutaneous B-cell lymphomas (PCBCLs) account for 25% of all primary cutaneous lymphomas. Three major types are currently recognized by the WHO classification: primary cutaneous marginal zone B-cell lymphoma (PCMZL), primary cutaneous follicle centre lymphoma (PCFCL) (both considered indolent lymphomas) and primary cutaneous diffuse large B-cell lymphoma, leg-type (PCDLBCL-LT), which is, instead, a very aggressive disease. Nowadays, the PCBCL’s category also includes some rare entities such as intravascular B-cell lymphoma (IVBL) and the EBV+ mucocutaneous ulcer (EBVMCU). Furthermore, controversies still exist concerning the category of primary cutaneous diffuse large B-cell lymphoma (PCDLBCL), because some cases may present with clinical and histological features between PCFCL and PCDLBCL-LT. Therefore, some authors proposed introducing another category called PCDLBCL, not otherwise specified (NOS). Regardless, PCBCLs exhibit distinct features and differ in prognosis and treatment from their nodal/systemic counterparts. Therefore, clinicopathologic analysis is a key diagnostic element in the work-up of these lymphomas.